Factors derived from human exfoliated deciduous teeth stem cells reverse neurological deficits in a zebrafish model of Parkinson's disease - Yong-Ren Chen; Chin-Chean Wong; Yi-No Chen; Bing-Heng Yang; Po-Hui Lee; Chia-Yang Shiau; Kuo-Chuan Wang; Chung-Hsing Li (Elsevier, 2024)
Background/purpose: Mesenchymal stem cells exhibit therapeutic efficacy for brain injury. This study examined the effect of mesenchymal stem cells derived from human exfoliated deciduous teeth (SHED) on alleviating symptoms of Parkinson's disease (PD). Materials and methods: SHED were isolated to examine the biosafety and bioavailability of stem cells derived from human exfoliated deciduous teeth-derived conditioned medium (SHED-CM) for the alleviation of PD symptoms in a 6-hydroxydopamine (6-OHDA)-induced PD zebrafish model. Results: SHED-CM administration did not induce neurological, skin or muscle toxicity in control zebrafish at any dose, and estrogen equivalent testing showed no chronic toxicants. Induction of PD with 6-OHDA suppressed zebra SHED-CM was administered to zebrafish treated with 6-OHDA to induce PD symptoms. Similar to nomifensine, a drug with proven anti-PD potential, SHED-CM repaired the motor deficiencies in the zebrafish PD model. Conclusion: Our results indicate the biosafety of SHED-CM and its therapeutic potential in treating PD in a zebrafish model.